Fermentable oligosaccharides, disaccharides, monosaccharides, and polyols (FODMAPs) and mortality among survivors of liver cirrhosis: a prospective cohort study - Danial Fotros; Azita Hekmatdoost; Fereshteh Pashayee-khamene; Sara Karimi; Saleheh Ahmadzadeh; Mehdi Saberifiroozi; Behzad Hatami; Zahra Yari (Nutrition Journal)
Abstract Background Cirrhosis is a medical condition marked by persistent liver damage, which leads to the development of fibrous tissue and compromised liver function. In the present study, we decided to investigate the possibility of a connection between the consumption of fermentable olig-, di-, monosaccharides, and polyols (FODMAPs) and mortality rates in cirrhotic patients by utilizing data obtained from a prospective cohort study. Methods This cohort study enrolled 166 ambulatory patients from two hospitals in Tehran, Iran, between 2016 and 2018, and followed them up for 5 48 months until April 30, 2022. During the 3,955 person-months of follow-up, 43 fatalities were recorded (36 men and 7 women). The study classified participants into three groups based on their FODMAPs consumption and assessed the risk of mortality using Cox proportional hazards regression models. Results Total FODMAPs intake was associated with increased overall mortality risk (T3 vs. T1, HR = 3.5; 95%CI: 1.05, 11.7; P-trend = 0.036). This significant trend was also observed for total fructans (T3 vs. T1, HR = 5.15; 95% CI: 1.15, 23.2; P-trend = 0.006) and fructose (T3 vs. T1, HR = 5.55; 95% CI: 0.54, 57.14; P-trend = 0.018). Mortality risk was U-shaped with galactooligosaccharide intake, a lower mortality risk was observed with lactose intake and a higher mortality risk with polyols intake, although these associations did not reach statistical significance. Conclusion In conclusion, this study highlights a higher risk of mortality with higher intake of fructans, excess fructose and total FODMAPs.